2022
DOI: 10.3389/fimmu.2022.1082414
|View full text |Cite
|
Sign up to set email alerts
|

MiR-451a and let-7i-5p loaded extracellular vesicles attenuate heme-induced inflammation in hiPSC-derived endothelial cells

Abstract: Hemolysis is associated with many pathologies, including trauma, sepsis, hemorrhagic stroke, malaria, and genetic disorders such as sickle cell disease (SCD). When hemolysis occurs, free-heme drives vascular inflammation, resulting in oxidative tissue damage and cardiometabolic complications. A better understanding of heme clearance and detoxification is essential to preventing sustained tissue damage. Human induced pluripotent stem cell (hiPSC)-derived endothelial cells (hiPSC-ECs) provide a novel source of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that heme may induce inflammation of endothelial cells. 23 To investigate whether heme can cause SIRS by inducing endothelial cell inflammation, human lung microvascular endothelial cells (HLMVECs) were treated with heme. Heme induced morphological changes in cells after heme treatment ( Figure 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that heme may induce inflammation of endothelial cells. 23 To investigate whether heme can cause SIRS by inducing endothelial cell inflammation, human lung microvascular endothelial cells (HLMVECs) were treated with heme. Heme induced morphological changes in cells after heme treatment ( Figure 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, let-7i-5p overexpression repressed hypoxia-induced NF-κB activation, mitochondrial dysfunction and cardiomyocyte apoptosis [ 54 ]. Let-7i-5p-loaded extracellular vesicles attenuated heme-induced inflammatory injury in heme-derived endothelial cells [ 55 ]. We found that elevated ssc-let-7i-5p inhibited apoptosis, inflammatory injury and barrier dysfunction in IPEC-J2 cells caused by CPB2 toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was completed using GraphPad Prism version 10.0.0 for Windows (GraphPad Software, La Jolla, CA, USA). The ∆∆CT method was used to identify mRNA gene expression [48]. Normality was checked using a Shapiro-Wilk normality test.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of miRNA in liposomes was 400 pmol. The expression of miRNAs let-7i-5p and miR-451a was an influence on heme-induced inflammation [48].…”
Section: Liposome Formulationmentioning
confidence: 99%